2006
DOI: 10.1029/2005wr004617
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of lateral flow in unsaturated homogeneous isotropic sloping soil due to rainfall

Abstract: This paper describes laboratory experimental evidence for lateral flow in the top layer of unsaturated sloping soil due to rainfall. Water was applied uniformly on horizontal and V‐shaped surfaces of fine sand, at rates about 100 times smaller than the saturated hydraulic conductivity. Flow regimes near the surface and in the soil bulk were studied by using dyes. Streamlines and streak lines and wetting fronts were visually studied and photographed through a vertical glass wall. Near wetting fronts the flow di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 27 publications
4
52
0
Order By: Relevance
“…Lateral unsaturated flow has been detected in soils in the field (Genereux, Hemond, & Mulholland, ; Jackson, ; Logsdon, ; McCord, Stephens, & Wilson, ; Ridolfi, D'odorico, Porporato, & Rodriguez‐Iturbe, ; Torres, Dietrich, Montgomery, Anderson, & Loague, ) and laboratory (Cabral, Garrote, Bras, & Entekhabi, ; Lv, Hao, Liu, & Yu, ; Sinai & Dirksen, ). The resulting unsaturated water fluxes offer a process description for unsaturated soils supplying baseflow to streams (Anderson & Burt, ; Hewlett, ; Hewlett & Hibbert, ) and the variation of soil moisture with topography (Perry & Niemann, ).…”
Section: Introductionmentioning
confidence: 99%
“…Lateral unsaturated flow has been detected in soils in the field (Genereux, Hemond, & Mulholland, ; Jackson, ; Logsdon, ; McCord, Stephens, & Wilson, ; Ridolfi, D'odorico, Porporato, & Rodriguez‐Iturbe, ; Torres, Dietrich, Montgomery, Anderson, & Loague, ) and laboratory (Cabral, Garrote, Bras, & Entekhabi, ; Lv, Hao, Liu, & Yu, ; Sinai & Dirksen, ). The resulting unsaturated water fluxes offer a process description for unsaturated soils supplying baseflow to streams (Anderson & Burt, ; Hewlett, ; Hewlett & Hibbert, ) and the variation of soil moisture with topography (Perry & Niemann, ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on their experiments for large and small soil boxes, Sande and Chu (2012) concluded that the wetting front movement was "faster" under higher peaks and smooth surfaces compared with the adjacent lower depressions, and that the microtopographic effects on wetting front movement were still strong for deeper soil and longer-duration rainfall. Sinai and Dirksen (2006) observed that during the initial stage of percolation, the wetting front was parallel to the soil surface. As the front moved deeper, the effect of soil surface microtopography became weaker and the wetting front became horizontally homogeneous.…”
Section: Microtopographic Impact On Unsaturated Flowmentioning
confidence: 95%
“…Surface microtopography induces lateral flow movement near the soil surface, and this movement degenerates along soil depth (Sinai and Dirksen 2006). However, gravity force gradually becomes the governing force over time (Hillel 1998;Sande and Chu 2012).…”
Section: Microtopographic Impact On Unsaturated Flowmentioning
confidence: 99%
“…6 -60 min). Sinai and Dirksen (2006) described, with laboratory experiments for an unsaturated homogeneous slope, that the flow direction during early wetting may be directed upslope, and during a flow regime of steady infiltration, the flow vector is changed toward the vertical direction. Already after 1 h 35 min, a clear change of the orientation into the vertical direction is recognizable (Fig.…”
Section: Discussionmentioning
confidence: 99%